2014
DOI: 10.1002/2013gl058636
|View full text |Cite
|
Sign up to set email alerts
|

On the long‐term stability of Gulf Stream transport based on 20 years of direct measurements

Abstract: In contrast to recent claims of a Gulf Stream slowdown, two decades of directly measured velocity across the current show no evidence of a decrease. Using a well-constrained definition of Gulf Stream width, the linear least square fit yields a mean surface layer transport of 1.35 × 10 5 m 2 s À1 with a 0.13%negative trend per year. Assuming geostrophy, this corresponds to a mean cross-stream sea level difference of 1.17 m, with sea level decreasing 0.03 m over the 20 year period. This is not significant at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 27 publications
9
77
0
Order By: Relevance
“…Daily maps are averaged to produce monthly maps from 1993 to the end of 2014. For each month, the Gulf Stream path is identified with the 25 cm sea surface height (SSH) contour (consistent with Lillibridge and Mariano [2013] and Rossby et al [2014]; see also Text S1 in the supporting information for a discussion of different methods to identify the Gulf Stream location with satellite altimetry).…”
Section: Identifying the Gulf Stream Path And Its Transition To An Unmentioning
confidence: 88%
“…Daily maps are averaged to produce monthly maps from 1993 to the end of 2014. For each month, the Gulf Stream path is identified with the 25 cm sea surface height (SSH) contour (consistent with Lillibridge and Mariano [2013] and Rossby et al [2014]; see also Text S1 in the supporting information for a discussion of different methods to identify the Gulf Stream location with satellite altimetry).…”
Section: Identifying the Gulf Stream Path And Its Transition To An Unmentioning
confidence: 88%
“…Understanding the structure and behavior of the western boundary current is a key problem in climate dynamics. However, despite observational evidence in recent years of the western boundary current deviating outside established meander envelopes (Gawarkiewicz et al 2012;Ezer et al 2013), ongoing debates over possible recent changes in Gulf Stream transport (Ezer et al 2013;Rossby et al 2014), and forecasts of changes in the meridional overturning as a consequence of anthropogenic climate change (e.g., IPCC 2007, and references therein), there remain many unknowns about the structure and variability of the western boundary current under the current climate.…”
Section: Introductionmentioning
confidence: 99%
“…Ezer et al (2013) analyzed the MSL elevation gradient across the western boundary of the Gulf Stream, Florida Current transport, and coastal sea level at 10 tide gauges in the Chesapeake Bay and middle Atlantic coast concluding that the Gulf Stream has shifted from a 6-8 year oscillation cycle to a continuous weakening trend since about 2004, and that this trend may be responsible for a recent acceleration of middle Atlantic coast sea level rise (Sallenger et al, 2012). Subsequently, Rossby et al (2014) reported 2 decades of ship-based velocity measurements across the Gulf Stream finding no significant decrease based on a linear regression. We note that Ezer et al (2013) based their results on empirical mode decomposition (EMD), a component of the Hilbert-Huang transform (Huang and Wu, 2008) capable of extracting nonlinear trends, in an area limited to the US east coast, while Rossby et al (2014) analyzed stream-wide transects from the east coast to Bermuda.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Rossby et al (2014) reported 2 decades of ship-based velocity measurements across the Gulf Stream finding no significant decrease based on a linear regression. We note that Ezer et al (2013) based their results on empirical mode decomposition (EMD), a component of the Hilbert-Huang transform (Huang and Wu, 2008) capable of extracting nonlinear trends, in an area limited to the US east coast, while Rossby et al (2014) analyzed stream-wide transects from the east coast to Bermuda. More recently, Ezer (2015) re-examined this apparent tension finding that the contrasting results are actually consistent when one considers the nonlinear nature and spatial dependence of the data.…”
Section: Introductionmentioning
confidence: 99%